Comparision of usability evaluation of public administration webpages by user testing and by analytical models - Hub, Miloslav; Musilová, Barbora (Univerzita Pardubice, 2016)
The usability of user interfaces especially of webpages is currently a very hot topic. The existing scientific literature contains various methods for testing and evaluation of the usability of various user interfaces. The benefit of various usability evaluation methods is described in this article, especially evaluation of usability by models and user testing. The most commonly used methods for these purposes are usability testing and heuristic evaluation. However, there are also suggestions of usability evaluation through analytical models that allow us to evaluate usability without having to involve end-users or experts in this evaluation process. These methods and their applicability are described in the article as well. For the purposes of the research as representative websites of public administration were chosen websites of selected municipalities. Next, the paper deals with evaluation of the web pages of selected statutory cities usability where the usability is evaluated by both suggested and validated analytical model and usability testing. The main goal is to compare the results of usability evaluation by analytical models and usability testing that use real end users and to check the analytical model’s ability to act like in a real situation.
Keywords: analytical models; usability; usability engineering; usability evaluation; user interfaces; user testing; C88; H83; L86